Challenges Faced by English Teacher in Implementing Independent Curriculum at MTs Darul Makmur Sungai Cubadak Academic Year 2023/2024 - Ari Saputra; Julia Anugerah Putri; Rianto Rianto (JEICI - Journal of Education and Islamic Contemporary Issue, 2025)
The research aims to discover English teachers' challenges in implementing an independent curriculum at MTs S Darul Makmur Sungai Cubadak academic year 2023/2024. The study used qualitative research by interviewing three English teachers at MTs S Darul Makmur Sungai Cubadak who were implementing an independent curriculum. The result showed that the teachers interviewed had convincing evidence about their challenges in implementing an independent curriculum During teaching and learning activities. The form of an independent curriculum is new for teachers because they never get to know and learn during their studies. So, the change from curriculum 13 to independent curriculum challenged the teacher. Almost all the respondents faced challenges in implementing an independent curriculum, such as designing teaching modules, class management, learning projects, and doing assessments based on an independent curriculum.